Effects of Vitamin E on Fasting and Postprandial Oxidative Stress, Inflammatory Markers, Glucose Status, Insulin Resistance, Blood Pressure and Pulse Rate in Type-2 Diabetic Patients: A Randomized Clinical Trial: - Mazloom, Zohreh; Hejazi, Najmeh; Dabbaghmanesh, Mohammad Hossein; Dashtabi, Arash (Galen Medical Journal, 2015)
Background: Atherosclerosis is one of the prevalent complications in diabetic patients. Increased free radical levels in diabetes activate stress-sensitive signaling pathway, resulting in this outcome. This study examines the effect of short-term supplementation of vitamin E on different biochemical markers in type 2 diabetic patients to prevent from atherosclerosis. Materials and Methods: In this single-blind placebo controlled trial, 30 type 2 diabetic patients were randomly divided into two groups of study to receive vitamin E (400IU) or identical placebo capsules daily for 6 weeks. Serum level of lipoproteins, glucose, insulin, malondialdehyde (MDA), interleukin-6 (IL-6), high-sensitivity C-reactive protein (hs CRP), pulse rate and blood pressure were measured in fasting and postprandial (after a fatty meal) states before and after six weeks of supplementation. Results: There was not any significant difference in fasting and postprandial lipid profile (Triglyceride, HDL-, LDL- and total Cholesterol), glucose, insulin and HOMA-IR after six weeks of intervention between the two groups. However, results of our study showed a significant decrease in fasting and postprandial MDA levels and postprandial pulse rate and a significant increase in fasting IL-6 in vitamin E group compared to the controls after supplementation. There were no significant differences between the groups in other markers. Conclusion: This study suggests that short term supplementation of vitamin E can reduce oxidative stress in fasting and postprandial states in type 2 diabetic patients and may prevent diabetic complications; in addition, increment of IL-6 after supplementation may play a role in attenuating Type 2 diabetes by anti-inflammatory effects.[GMJ. 2015;4(3):67-74]